1990
DOI: 10.5144/0256-4947.1990.140
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis: Experience in a University Hospital in Riyadh, Saudi Arabia

Abstract: In a retrospective study, all cases of patients with acute pancreatitis admitted consecutively to the University Hospitals in Riyadh over the five-year period 1984-1988 were analyzed. There were a total of 104 attacks in 91 patients. Mean patient age was 42.4 years and the female to male ratio was 1.5:1. In 67%, gallstones were the associated cause; idiopathic acute pancreatitis was diagnosed in only 11.5%. Among the 50 (55%) Saudi nationals, two thirds were females and 76% had biliary pancreatitis. Using modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…With regard to the incidence rate of AP between genders, many Saudi researchers over the last three decades have agreed that AP is more prevalent in males than in females, except for Allhebi et al, who found no significant gender differences [ 2 , 13 - 14 ]. However, our results, consistent with those of Allhebi et al, showed no significant difference in incidence rates between genders (p > 0.05; see Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the incidence rate of AP between genders, many Saudi researchers over the last three decades have agreed that AP is more prevalent in males than in females, except for Allhebi et al, who found no significant gender differences [ 2 , 13 - 14 ]. However, our results, consistent with those of Allhebi et al, showed no significant difference in incidence rates between genders (p > 0.05; see Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the present study and others cited, the role of ERCP in the diagnosis and management of ABP are discussed and recommendations suggested. In over 70% of attacks of acute pancreatitis (AP) among Saudi and non-Saudi patients, gallstones were the associated factor as recently reported from Riyadh by Laajam [1,2]. Early intervention in severe cases of gallstoneassociated AP by endoscopic retrograde cholangiopancreatography (ERCP) and sphincterotomy has been shown in a controlled trial to improve morbidity and mortality as compared with conservative treatment [3].…”
mentioning
confidence: 88%
“…Alcohol-induced AP is rarely seen in Saudi Arabia due to Islamic teachings [1,2]. AP is associated with serious complications in 20% to 30% of cases and death in 8% to 20%.…”
Section: Discussionmentioning
confidence: 99%
“…References: [12][13][14][15][16][17][18][19][20][21] These studies were conducted between 1985 and 2023. All included studies were conducted in Saudi Arabia and took place in three different regions.…”
Section: Additional Information Author Contributionsmentioning
confidence: 99%